The Effect of Various Sterilization Methods and Volume Containers on Phytochemical Content of Methanol Extract of Phyllanthus urinaria - Tri Novia Yuliana; Adhina Choiri Putri; Bambang Cahyono; Agustina L. N. Aminin (Jurnal Kimia Sains dan Aplikasi, 2023)
Phyllanthus urinaria is an annual perennial herbal species found in tropical Asia, America, China, and the Indian Ocean islands. Phyllanthus urinaria is used in folk medicine as a cure to treat jaundice, diabetes, malaria, and liver diseases. Sterilizing the substrate is a crucial step in the fermentation process. This process ensures that the inoculated microorganism is entirely single. Autoclave sterilization is widely favored within the scientific community. In autoclaving, pressurized steam is employed to deliver heat, effectively reducing the bioactive compounds present in the substrate. Comparative studies on various sterilization methods have been reported. This study aims to investigate the effects of substrate containers in sterilization methods of the herbal plant on phenol and flavonoid compounds by LC-MS (Liquid Chromatography-Mass Spectrometry) analysis. Three sterilization methods (pasteurization, steam, and autoclave sterilization) were each applied to the meniran herbal plant (Phyllanthus urinaria) for 15 minutes. Using the aluminum chloride colorimetric assay, the sterilization results were measured for total phenol content, the Folin-Ciocalteu test, and total flavonoid content. The LC-MS analysis showed that the methanol extract of Phyllanthus urinaria (APU) sterilized by autoclaving resulted in the most significant reduction in active phenolic and flavonoid compounds. Pasteurization, steaming, and autoclaving in a big container resulted in total flavonoid content of 1.80±0.034, 1.70±0.021, and 1.71±0.029 mg QE/g extract. The total phenolic content was 26.49±0.591, 22.77±0.230, and 22.097±0.155 mg GAE extract/g, respectively. Meanwhile, using a small container, each method produced a total flavonoid content of 1.73±0.024, 1.71±0.051, and 1.62±0.015 mg QE/g extract, respectively. The total phenolic content was 20.56±0.093, 19.79±0.295, and 20.09±0.124 mg GAE/g extract. Furthermore, the LC-MS profile revealed that APU experienced a reduction in ρ-hydroxybenzaldehyde and naringenin compounds, leading to a decrease in rutin, methyl brevifolincarboxylate, and ethyl gallate compounds. From the results of LC-MS analysis, this research determined that pasteurization using a big container is the most effective sterilization method for preserving the highest levels of total flavonoid and phenolic content in Phyllanthus urinaria while minimizing adverse effects on phytochemical compounds.